Infestation and damage status assessment of white mango scale (Aulacaspis tubercularis) insect at boloso sore and boloso bombe districts of Wolaita Zone South Ethiopia - Andualem Alemayehu; Zerhun Tomas (International Journal of Agricultural Research, Innovation and Technology, 2025)
This fruit devastating pest of white mango scale (Aulacaspis tubercularis Newstead; Hempitera: Diaspididae) insect is an economically important pest and damages the mango fruit by sucking the sap through its piercing-sucking mouth part from mango leaves and fruits. Since the 2010 outbreak in Ethiopia due to a poor internal quarantine system this insect pest was distributed and invaded the whole mango-producing region in the country. Therefore, the aim of this study was to assess the infestation and severity status of WMS insects to get evidence for upcoming management investigations. The survey was carried out at Boloso Bombe and Boloso Sore districts in South Ethiopia Wolaita Zone in 2023. Among mango-producing farmers by using a semi-structural questionnaire 45 farmers were intervened through random selection. Geographic location and ten samples of mango leaf were collected from four cardinal directions per tree of each stop for examining the infestation and severity status of WMS. The occurrence of this pest at study locations was in 2016 as interviewed farmers respond. Since then, due to a lack of attention by farmers currently, it was distributed and covered the whole study area. As confirmed by this study the infestation ranged from 60 to 100% and damage or severity rated from moderate to very high. Among surveyed locations, 29% of mango farms were very highly, 52% highly and 20% moderately damaged. From the total study area, almost 31% of mango farms reduced 100% yield and the reduction of yield ranged from 50% to 100%. Before the outbreak of this invasive insect pest, the study area farmers were harvesting nearly 272 kg of mango fruit per tree and at normal times yield reduction was almost 43 kg per tree. After the prevalence of WMS insect per tree yield was almost 44 kg and the reduction of yield was alarmingly increased to 228 kg per tree as shown by this study data. Even though this insect pest is a devastating pest of mango fruit, however, it can be controlled through different management practices. Therefore, the management practice of this pest is categorized into three such as cultural, biological and biochemical. Culturally managed by Mango tree pruning, planting resistant materials, using proper spacing, cleaning or sanitation, burying infected residues and fruits, smoking different repellents of dry grass, animal dung, mango leaves and lemon bark or lemon mixed organic materials in one smoking can/pot and hanging inside mango tree. Foliar Spraying of various botanical extracts such as Neem seed extract (Azadirachta indica). Several concoctions made from ash, soap and goat urine were mixed and sprayed on infested mango fruit leaves and twigs. Various predators and parasitoids are used as Biological control. Soil drenching of systemic chemical insecticides also can control this insect pest. The way to control this serious damage and hinder the expansion of this invasive insect pest, integrated experimental investigation using the above-explained mechanisms will be advisable to enhance mango fruit yield. Int. J. Agril. Res. Innov. Tech. 14(2): 28-37, December 2024